If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 6 + -3y = 3 Reorder the terms: 6 + -3y + -3y = 3 Combine like terms: -3y + -3y = -6y 6 + -6y = 3 Solving 6 + -6y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -6y = 3 + -6 Combine like terms: 6 + -6 = 0 0 + -6y = 3 + -6 -6y = 3 + -6 Combine like terms: 3 + -6 = -3 -6y = -3 Divide each side by '-6'. y = 0.5 Simplifying y = 0.5
| -20m-12=80 | | 5(-8+x)+6x=-128 | | -4.5=0.5-5y | | -20t+10t-8t-5t= | | 35=24.5 | | (x-2)(x-4)=15 | | -42m-13=83 | | -192=-6(6x-4) | | 18x^2-12x^3+18=0 | | 633=9x+318 | | 18=w | | 18x^2-12x^3+3=0 | | G(-3)=3-27-3 | | 8^1/4-5^2/3 | | 84=4(1-4g) | | (b^4)^1/9=dsqrt(b^4) | | 2x+1.4=5.6 | | -1.2=1.8-3y | | 18=w/0.2 | | -9m-9=102 | | 587=8x+387 | | -2.8=5.2-2y | | -(-8x+4)+9x= | | -25=5(y-4) | | 4h-6=10n | | -12m-8=70 | | 0.16666666666(12-6x)=5(x+4) | | 0.33333333333(6y-9)=-2y+13 | | 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) |